Pengaruh Kualitas Produk, Citra Merek, dan Promosi Penjualan terhadap Keputusan Pembelian Produk Somethinc oleh Generasi Z melalui Platform Shopee di Kabupaten Bandung - Salsabila, Annisa; Karamang, Ezra; Muttaqin, Ridlwan (J-MAS (Jurnal Manajemen dan Sains), 2025)
Consumers' choices to purchase Somethinc things are influenced by product quality, brand image, and sales promotion. This research aims to analyze and assess these factors. The study population includes Somethinc product users; specifically, it includes a sample of Bandung Regency residents from Generation Z, ranging in age from 18 to 28, who have purchased Somethinc goods. The sample size was 120 people. Multiple linear regression was one of the data analysis strategies used using SPSS version 25, and the research instruments were evaluated using a Likert scale ranging from 1 to 5. Brand perception and product quality were shown to have a substantial and positive effect on customers' purchasing choices. Conversely, the variabel of sales promotion had no impact on the choice to purchase Somethinc items.